The Analysis of Water Meter Application with Approach of Overall Equipment Effectiveness in Municipal Waterworks Bali - Ariadi, Gede; Abdi, Antonius Surjo; Putri , Christina Ari Pramono (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2023)
Companies in this globalization era face many problems. One of them is productivity, performance, and customer service. The companies must try to keep the quality. The Total Productive Maintenance (TPM) strategy is a system used to improve equipment quality based on a maintenanceapproach, which can be an effective solution. However, problems were occurring in the Municipal Waterworks business system due to Overall Equipment Effectiveness (OEE) which was not optimal. The solution must be to have an application system that can be used to measure and monitor the performance of water meter readers. This study used data focused on OEE, which began with TPM, which aimed to discover the problems in the maintenance of the municipal waterworks company. SPSS is software used to analyze data collection. SPSS data showed that the highest score is87.61 and 84.21 based on descriptive statistics for the maximum and average scores. This data indicates that OEE is an application vital to the company’s quality. Pearson correlation showed that the availability aspect gave more significant results than the performance and quality aspects.OEE provides benefits in developing equipment performance by analyzing equipment performance and effectively and efficiently checking six big losses. Therefore, the implementation of strategy production with TPM is a combination that provides benefits in a more flexible water meter system and customers who are satisfied with the service from company.